5(2t-3)+4t=30-t

Simplify each term.

Apply the distributive property.

5(2t)+5⋅-3+4t=30-t

Multiply 2 by 5.

10t+5⋅-3+4t=30-t

Multiply 5 by -3.

10t-15+4t=30-t

10t-15+4t=30-t

Add 10t and 4t.

14t-15=30-t

14t-15=30-t

Add t to both sides of the equation.

14t-15+t=30

Add 14t and t.

15t-15=30

15t-15=30

Add 15 to both sides of the equation.

15t=30+15

Add 30 and 15.

15t=45

15t=45

Divide each term in 15t=45 by 15.

15t15=4515

Cancel the common factor of 15.

Cancel the common factor.

15t15=4515

Divide t by 1.

t=4515

t=4515

Divide 45 by 15.

t=3

t=3

Solve for t 5(2t-3)+4t=30-t